New screening and quantification method by UHPLC-MS/MS of 36 new synthetic cathinones in hair. Application to real cases - Alfredo Fabrizio Lo Faro; Anastasio Tini; Giorgi Kobidze; Giulio Mannocchi; Massimo Gottardi; Francesco Paolo Busardò; Giuseppe Basile; Bezhan Chakvetadze (Journal of Pharmaceutical and Biomedical Analysis Open)
A class of β-keto analogs of phenethylamine known as synthetic cathinones has been identified as the most emergent new class of psychoactive chemicals in the last ten years. Synthetic cathinones (SC) are becoming more varied, which represents a serious danger to social security and public health worldwide. In this work, an analytical technique based on UHPLC-MS/MS was developed for the simultaneously measurement of 36 synthetic cathinones and two metabolites in hair keratin samples. The separation was conducted by Atlantis Premier BEH C18 AX (2.5 μm, 2.1 × 100 mm) column using elution with 5 mM ammonium acetate in water with 0.1 % formic acid (v/v) (mobile phase A) and 2 mM ammonium formate in MeOH/Acetonitrile 50/50, +0.1 % formic acid (v/v) (mobile phase B). The analysis time was 11 min. Mass spectrometer was equipped with electrospray ionization (ESI). Multiple reaction monitoring (MRM) mode was used for the detection and quantification of the studied compounds. The methodology was successfully validated according to the Organization Scientific Area Committee guidelines, with linearity (r2 ≥ 0.99) from LOQ to 500 pg/mg concentrations for all the compounds investigated. This method was subsequently applied to nine hair samples positive for ten different synthetic cathinones. The most common SCs identified were 3,4-methylenedioxypyrovalerone (3,4-MDPV), in a concentration range 6.0–1000.0 pg/mg, along with alpha-pyrrolidinopentiophenone (α-PHP (54.0 and 554.0 pg/mg, respectively)), followed by the two positional isomers 3-MMC (556.0 and 5000.0 pg/mg) and 4-MMC (11.5 and 448.0 pg/mg). In conclusion, a validated LC-MS/MS method with high specificity was developed offering an easy and affordable sample preparation, and a run time that makes it suitable for use in a high throughput forensic laboratory for the multi-analyte quantification of 36 novel synthetic cathinones and 2 metabolites in hair.